Forms of List-Making: Epistemic, Literary, and Visual Enumeration - Barton, Roman Alexander; Böckling, Julia; Link, Sarah; Rüggemeier, Anne (Springer Nature, 2022)
This open access book attempts to show that an examination of the list's formal features has the potential to produce genuine insights into the production of knowledge, the poetics of literature and the composition of visual art. Following a conceptual introduction, the twelve single-authored chapters place the list in a variety of well-researched contexts, including ancient Roman historiography, medieval painting, Enlightenment periodicals, nineteenth-century botanical geography, American Beat poetry and contemporary photobooks. With its interdisciplinary approach, this book is a unique contribution to an emerging field dedicated to the study of lists.